2019
DOI: 10.1111/jnc.14894
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C improves blood–brain barrier integrity after ischemic brain injury in mice

Abstract: Cystatin C, a well-established biomarker of renal function, has been associated with a protective effect against stroke. However, the potential neuroprotective mechanism of cystatin C in ischemic brain injury remains unclear. Our study hypothesized that cystatin C can ameliorate blood-brain barrier (BBB) disruption by up-regulating caveolin-1 expression, thereby improving neurological outcomes in cerebral ischemic injury. Western blotting, immunohistochemistry, immunofluorescence staining, and immunoprecipitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 33 publications
4
9
0
Order By: Relevance
“…increased, suggesting that caveolin-1 might play a protective role by inhibiting the expression of MMP-9. The results of our study are similar to that of a recent research conducted by Yang et al [36], they showed that the expression of caveolin-1 was up-regulated in MCAO-injured mice, and pretreatment with cystatin C could further increased caveolin-1 and decreased the enzymatic activity of MMP-9. The up-regulation of caveolin-1 during ischemia may be a protective compensatory response to prevent brain damage.The positive correlation between caveolin-1 expression and functional de cit may be related to the compensatory increase of caveolin-1during ischemia.…”
Section: Discussionsupporting
confidence: 92%
“…increased, suggesting that caveolin-1 might play a protective role by inhibiting the expression of MMP-9. The results of our study are similar to that of a recent research conducted by Yang et al [36], they showed that the expression of caveolin-1 was up-regulated in MCAO-injured mice, and pretreatment with cystatin C could further increased caveolin-1 and decreased the enzymatic activity of MMP-9. The up-regulation of caveolin-1 during ischemia may be a protective compensatory response to prevent brain damage.The positive correlation between caveolin-1 expression and functional de cit may be related to the compensatory increase of caveolin-1during ischemia.…”
Section: Discussionsupporting
confidence: 92%
“…The results of our study are similar to that of a recent research conducted by Yang et al [35], they showed that the expression of caveolin-1 was up-regulated in MCAO-injured mice, and pretreatment with cystatin C could further increased caveolin-1 and decreased the enzymatic activity of MMP-9. The up-regulation of caveolin-1 during ischemia may be a protective compensatory response to prevent brain damage.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, after the administration of daidzein, the level of caveolin-1 decreased, while the level of MMP-9 increased, suggesting that caveolin-1 might play a protective role by inhibiting the expression of MMP-9. The results of our study are similar to that of a recent research conducted by Yang et al [40], they showed that the expression of caveolin-1 was up-regulated in MCAO-injured mice, and pretreatment with cystatin C could further increased caveolin-1 and decreased the enzymatic activity of MMP-9. The up-regulation of caveolin-1 during ischemia may be a protective compensatory response to prevent brain damage.…”
Section: Discussionsupporting
confidence: 92%